The prospects of application of spring chistyak Ficaria verna huds in medicine and food industry, chemical composition and biological activity - D. A. Konovalov; D. S. Zolotykh; D. I. Pozdnyakov (Современная наука и инновации)
Ficaria verna is a perennial herbaceous invasive plant widely distributed in Russia. Phenolic (flavonoids, phenolic acids), terpene (triterpene, carotenoids, phytosterols, phthalates) compounds are described as the main groups of biologically active compounds of its aerial part.The plant was used in folk medicine in some European countries in the treatment of cough, scurvy, hemorrhoids, and also as a hepatoprotective agent. As a toxic substance contained in the plant, protoanemonin is described - an unstable volatile lactone, which is easily converted into a non-toxic compound anemonin.The study of various extracts from Ficaria verna made it possible to establish their antioxidant, antiinflammatory and antimicrobial activity, which is of undoubted interest for further in-depth study.The review presents scientific data obtained from available open sources of literature containing information on biologically active substances of a widespread spring chistyak plant. In addition, information is provided on the use of this species and extracts based on it in folk and scientific medicine, established biological and pharmacological activity and toxicity.